Two genera and one species newly recorded with description of five new species of the subfamily Microgastrinae (Hymenoptera: Braconidae) from Vietnam - Long, Khuat Dang; Achterberg, C. Van (Academia Journal of Biology, 2014)
The genera Alloplitis Nixon, 1965 and Protapanteles Ashmead, 1898 (subgenus Nyereria Mason, 1981) (Braconidae: Microgastrinae) are newly recorded for Vietnamese fauna. Three valid species of the genus Alloplitis Nixon, 1965 and one species of the subgenus Nyereria Mason [15] are currently recognized from the Oriental region, and in this paper one species is newly recorded for the fauna of Vietnam, Alloplitis guapo Nixon, 1965 and five new species are described and illustrated from Vietnam, Alloplitis albiventris Long & van Achterberg, sp. n., A. laevigaster Long & van Achterberg, sp. n., A. vietnamicus Long & van Achterberg, sp. n., Protapanteles (Nyereria) albicentrus Long & van Achterberg, sp. n. and P. (Nyereria) yenthuyensis Long & van Achterberg, sp. n.. In collections these genera are rare, probably because Braconidae has been only limited collected by Malaise traps in Vietnam. For recognition of the subfamily Microgastrinae, see Nixon (1965) [10], for division of groups of the genus Apanteles s. l. see Wilkinson (1932) and Nixon (1965, 1967), for reclassification of the subfamily Microgastrinae see Nixon (1965) and Mason (1981). For the terminology used in this paper, see van Achterberg (1993). The scale-lines of the plates indicate 1 mm.